2016
DOI: 10.1016/j.corsci.2016.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitor-loaded conducting polymer capsules for active corrosion protection of coating defects

Abstract: This work presents the synthesis of nanostructured hollow polyaniline (PANI) capsules and their application for encapsulation of corrosion inhibitor 2-Mercaptobenzothiazole (MBT). The pHtriggered release of MBT from the capsules was evidenced using UV-vis and Surface Enhanced Raman Spectroscopy (SERS). Incorporation of MBT loaded PANI capsules into epoxy ester coating on AA2024-T3 resulted in a protective system with self-healing ability confirmed by Electrochemical Impedance Spectroscopy (EIS) and Scanning Vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
64
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 136 publications
(70 citation statements)
references
References 54 publications
(67 reference statements)
0
64
0
2
Order By: Relevance
“…90 nm. The FTIR and UV-vis spectroscopies [13,16] showed that the capsules have a backbone polymer structure of polyaniline in an emeraldine salt form.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…90 nm. The FTIR and UV-vis spectroscopies [13,16] showed that the capsules have a backbone polymer structure of polyaniline in an emeraldine salt form.…”
Section: Resultsmentioning
confidence: 99%
“…UV-vis and SERS spectroscopies were used in the previous work [13] to con rm the encapsulation of MBT in PANI containers. In brief, after the encapsulation procedure, the capsules were washed and centrifuged for several times; then, the supernatant of washing of the capsules was studied using UV-vis spectroscopy.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations